Analisis Pengukuran Kinerja Value For Money pada Badan Pengelola Keuangan dan Aset Daerah Kabupaten Blitar - Amelia Ika Pratiwi; Ela Nursandia (Program Pendidikan Vokasi Universitas Brawijaya, 2017)
This study aims to analyze and measure performance by using the method of Value For Money at the Regional Financial and Asset Management Agency Blitar District which consists of economic, efficiency and effectiveness in the program implemented in the Regional Financial and Asset Management Agency Blitar regency. The results of this study for the economy, the overall existing activities can already be said to be economical because the budget realsasi smaller than the existing target. For efficiency level BPKAD Kabupaten Blitar period 2015-2016 has run its programs related to the efficient management of regional assets. While the effectiveness of effectiveness measurement based on Performance Indicators relating to the management of regional assets. Two years of the period there are two performance indicators: Percentage of Certification of Land Assets of Regency Government and Percentage of Regional Assets that have been managed. Both performance indicators, on the percentage of local assets that have been managed effectively and on the Percentage of Certification of Land assets of the District Government is required evaluation because the achievement is still below the existing target.